Who was Jesus? - Wright, Nicholas Thomas, 1948- (London, UK SPCK, 1992)
Contents : Preface - the portraits and the puzzles - Barbara Thiering: Jesus in code - A.N. Wilson: a moderately pale Galilean - John Spong: the bishop and the birth - Jesus revisited.
Keywords: Thiering, Barbara Elizabeth -- 1930-; Wilson, A. N., -- 1950-; Spong, John Shelby, -- 1931-; Jesus Christ -- person and offices; Jesus Christ -- history of doctrines -- 20th century